An in vitro skin sensitization assay termed EpiSensA for broad sets of chemicals including lipophilic chemicals and pre/pro-haptens. (April 2017) - Saito, Kazutoshi; Takenouchi, Osamu; Nukada, Yuko; Miyazawa, Masaaki; Sakaguchi, Hitoshi
Abstract: To evaluate chemicals (e.g. lipophilic chemicals, pre/pro-haptens) that are difficult to correctly evaluate using in vitro skin sensitization tests (e.g. DPRA, KeratinoSens or h-CLAT), we developed a novel in vitro test termed "Epidermal Sensitization Assay: EpiSensA" that uses reconstructed human epidermis. This assay is based on the induction of multiple marker genes (ATF3, IL-8, DNAJB4 and GCLM) related to two keratinocyte responses (inflammatory or cytoprotective) in the induction of skin sensitization. Here, we first confirmed the mechanistic relevance of these marker genes by focusing on key molecules that regulate keratinocyte responses in vivo (P2X7 for inflammatory and Nrf2 for cytoprotective responses). The up-regulation of ATF3 and IL-8, or DNAJB4 and GCLM induced by the representative sensitizer 2, 4-dinitrochlorobenzene in human keratinocytes was significantly suppressed by a P2X7 specific antagonist KN-62, or by Nrf2 siRNA, respectively, which supported mechanistic relevance of marker genes. Moreover, the EpiSensA had sensitivity, specificity and accuracy of 93%, 100% and 93% for 29 lipophilic chemicals (logKow ≥ 3.5), and of 96%, 75% and 88% for 43 hydrophilic chemicals including 11 pre/pro-haptens, compared with the LLNA. These results suggested that the EpiSensA could be a mechanism-based test applicable to broad sets of chemicals including lipophilic chemicals and pre/pro-haptens. Highlights: We developed a skin sensitization assay with reconstructed human epidermis. All the marker genes (ATF3, DNAJB4, GCLM and IL-8) were mechanistically relevant. 27 lipophilic chemicals and 12 pre/pro-haptens were correctly evaluated. The EpiSensA might be useful to estimate potency classification based on LLNA EC3.